Can proactively confessing obtain your embrace? Exploring for leader’s pro-social rule-breaking consequences based on a self-verification perspective - Wang, Fan; Weng, Haolin; Yang, Peilin; Li, Yi; Zhang, Man; Das, Anupam Kumar (Frontiers in Psychology, 2023)
The effect of leader pro-social rule breaking on employees is a critical albeit underexplored topic within the domain of study on the consequences of pro-social rule breaking in organizations. This paper attempts to make up for the gap by exploring the relationship between leader pro-social rule breaking and employee voice. Drawing on the theory of self-verification, we theorize that leaders who perform pro-social rule breaking will seek feedback from their subordinates, while employees being sought will be triggered to voice upwardly, the extent to which intensity of voice is moderated by the moral courage of employees. 283 dyads data of supervisor-subordinate from Shanghai, China in a three-wave time-lagged survey provided support for our hypotheses. The results show that leader pro-social rule breaking is positively related with leader feedback-seeking which is positively related with employee upward voice and mediates the relationship between the two. Moreover, the positive relationship between leader pro-social rule breaking and leader feedback-seeking as well as the indirect effect of leader pro-social rule breaking on employee upward voice via leader feedback-seeking was weakened when moral courage is high. The present study promotes the theoretical research on the positive results of leader pro-social rule breaking, and also suggests that feedback-seeking would be an effective way for leaders to motivate employees upward voice.